Spectroscopy of γ Doradus stars. Issue Volume 9:Issue S301(2013) (18th February 2014) - Brunsden, E.; Pollard, K. R.; Cottrell, P. L.; Wright, D. J.; De Cat, P.; Kilmartin, P. M.
Abstract: Themusician programme at the University of Canterbury has been successfully identifying pulsation modes in many γ Doradus stars using hundreds of ground-based spectroscopic observations. This paper describes some of the successful mode identifications and emerging patterns of the programme. The hybrid γ Doradus/δ Scuti star HD 49434 remains an enigma, despite the analysis of more than 1700 multi-site high-resolution spectra. A new result for this star is apparently distinct line-profile variations for the γ Doradus and δ Scuti frequencies.